The Influence of Nutrition in Pregnant Women on Breaking Postpartum at Puskesmas Inpatient Working Area in Bandar Lampung City - Sari, Ratna Dewi Puspita (Lighthouse Publishing, 2023)
Indonesia as a developing country still has nutritional problems, especially pregnancy nutrition. Malnutrition in pregnant women increases the risk of bleeding postpartum. This study was conducted to determine the effect of maternal nutritional status during pregnancy on the incidence of bleeding postpartum at the Bandar Lampung Inpatient Health Center. This research is an observational analytic by design case control. Samples, taken using the technique purposive sampling, divided into 61 cases and 122 controls at the Bandar Lampung Inpatient Health Center. The analysis was carried out using chi square and logistic regression test. The highest proportion of mothers giving birth at the Bandar Lampung Inpatient Health Center were mothers who were not at risk of CED (84.7%) and were not anemic (71.6%). There is a significant effect between the risk of chronic energy deficiency (CED) (p=0.001; OR=8.62) and anemia status (p=0.001; OR=9.54) on the incidence of bleeding postpartum. Anemia status (p=0.001; OR=11.41) is the variable with the strongest relationship to bleeding events postpartum. The highest proportion of mothers giving birth at the Bandar Lampung Inpatient Health Center were mothers who were not at risk of CED and were not anemic. The nutritional status of pregnant women including the risk of CED and anemia status affect the incidence of bleeding postpartum in birthing mothers. Variable with the strongest relationship to bleeding events postpartum is anemia status.